Innovative stealth marketing strategies and its ethical issues - DR. GIGI G S; MS. JAHNAVI. C (The journal of contemporary issues in business and government, 2020)
People have been bombarded by advertising for decades; every TV channel watched in, every social media page posted, every magazine opened, the advertisements are there. Audiences have grown with this.We have learned to filter messages, prevent advertisements from our views and minds, and exercise selective attention and concentrate on only what we want In fact, consumers now have the potential to ’protect’ themselves from different marketing ads with technology such as remote control, ad blockers, web filtering, and many more.From an ethical perspective, this paper will address the issue of stealth marketing within the scope of its practises. Issues to be addressed include the impact of stealth marketing on audiences, the rationale for the practise, and some recommendations. Here this study involves a descriptive research method as research design and samples for the finding purpose were collected from 85 respondents along with the help of primary data. The research findings were analyzed using tools like frequency analysis, mean analysis, independent t test and ANOVA analysis.